The Immunological Roles of Olfactory Ensheathing Cells in the Treatment of Spinal Cord Injury - Jiang, Yizhen; Guo, Jianbin; Tang, Xiangwen; Wang, Xiaohui; Hao, Dingjun; Yang, Hao (Frontiers in Immunology, 2022)
Spinal cord injury (SCI) is a devastating neurological disease of the central nervous system (CNS) with high mortality and morbidity. The pathological processes of SCI can be usually described as two stages, namely primary and secondary injuries. The secondary damage is more significant in exacerbations of initial injury. Among all the mechanisms of secondary damage, infection and inflammatory responses, as most principle culprits in initiating the second phase of SCI, can greatly contribute to the severity of SCI and numerous sequelae after SCI. Therefore, effectively antagonizing the pro-inflammatory responses may be a promising treatment strategy to facilitate functional recovery after SCI. Olfactory ensheathing cells (OECs), a unique population of glia, have recently emerged as potential candidates for cell-mediated repair in the injured CNS. Strikingly, there is growing evidence that the mechanisms underlying the anti-inflammatory role of OECs are associated with its own immune properties and secretory functions responsible for anti-neuroinflammation and immunoregulation, leading to maintenance of internal microenvironment. Accordingly, understanding the mechanism of OEC immunological functions in the treatment of SCI is beneficial to better consider the clinical therapeutic applications of OECs for SCI. In this review, we mainly summarize recent research regarding the cellular and molecular immune properties of OECs. Their biofunctions in promoting neural regeneration will be discussed for the development of novel therapies for CNS injury.